Polysomnographic correlates of self-and caregiver-reported sleep problems in post-stroke patients - Tayade, Kamalesh; Vibha, Deepti; Singh, Rajesh Kumar; Pandit, Awadh Kishor; Ramanujam, Bhargavi; Das, Animesh; Elavarasi, Arunmozhimaran; Agarwal, Ayush; Srivastava, Achal Kumar; Tripathi, Manjari (Frontiers in Neurology, 2025)
BackgroundPost-stroke sleep disorders (PSSD) are under-reported and under-treated, despite their impact on recovery, quality of life, and post-stroke depression. Although polysomnography (PSG) is the gold standard for diagnosis, its limited availability leads to underdiagnosis.AimsTo assess the prevalence of PSSD based on patient- and caregiver-reported data, and to evaluate their concordance with findings from overnight PSG in post-stroke patients.MethodsIn this cross-sectional study, adult patients (aged ≥18 years) with ischemic or hemorrhagic stroke (1 month to 1 year post-onset) were assessed. Sleep-related history was obtained from patients and caregivers. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI), risk of obstructive sleep apnea (OSA) was assessed with the STOP-BANG questionnaire, and depression and anxiety were evaluated with the Hamilton Depression Rating Scale (HAM-D) and Hamilton Anxiety Rating Scale (HAM-A), respectively. Stroke severity and outcomes were evaluated using the modified Rankin Scale (mRS) and Stroke-Specific Quality of Life Scale (SS-QoL). A subset underwent overnight PSG using a 14-channel SOMNOmedics system, analyzed per American Academy of Sleep Medicine (AASM) criteria. The Apnea-Hypopnea Index (AHI) was used to quantify sleep-disordered breathing.ResultsOut of 103 enrolled patients, 41 (39.8%) underwent PSG. While only 23.3% (n=24) of patients and 11.7% (n=12) of caregivers independently reported sleep disturbances after stroke, specific questioning increased detection to 62%. PSG revealed obstructive sleep apnea (OSA) in 62% of those denying sleep issues and in 100% of those self-reporting problems. Periodic limb movement disorder in sleep (PLMS) was present in 34.5% of asymptomatic individuals. Higher STOP-BANG scores and longer stroke duration were seen in the PSG group. Wakefulness after sleep onset (WASO) >120 minutes was more common in patients with PSQI >5. AHI >5 was present in 65.8%, but not associated with any demographic, clinical, or questionnaire-based variables.ConclusionThere is poor correlation between self/caregiver-reported sleep problems and PSG-confirmed diagnoses in post-stroke patients. Proactive screening using structured questionnaires and PSG (or alternatives such as actigraphy) is essential in resource-limited settings to detect and treat sleep disorders that may impact recovery.